Ecological and pollution studies of the British crayfish - Mees, Christopher Charles (1983)
The ecology of Austropotamobius pallipes (Lereboullet) from Markfield Quarry and the River Leen was described. Studies included: 1. Biology. (i) Timing of life cycle events. They related to ambient conditions, especially temperature. (ii) Fecundity. Individual fecundity increased with female size. Population fecundity related to population density. (iii) Local distribution. This related to hide availability. Gross water quality affected the distribution of the river crayfish. 2. Population dynamics. (i) Population size/density. That of the Quarry was greater, and related to hide availability. Seasonal variations in population size were temperature dependent. (ii) Population structure. - size structure varied between populations due to collection techniques. It varied seasonally due to recruitment and differential catchability of certain sub-populations. - sex ratios varied seasonally due to reduced foraging by ovigerous females. - disease and damage occurred for all sizes/sexes. Thelohania contejeanii was absent from Markfield Quarry but increased in the Leen during the study period. 3. Growth. (i) At moulting. Sexual differences were absent for the absolute increment, but males grew quicker due to greater moult frequencies. Growth rates of river animals were greatest due to a longer growing season and smaller population density. (ii) Relative growth of body parts. No consistent population differences occurred, but of significance were chelae and rostrum sizes. Sexual dimorphism occurred for certain variables, notably the chelae and abdomen width. The effects of cadmium and Lindane upon A. pallipes were examined. Studies included: 1. Survival. Juveniles were 10 times more sensitive than adults. Lindane was the most toxic. 2. Uptake and depuration. Cadmium accumulated chiefly in the gills. Some evidence for its translocation to other tissues was found. No sexual differences occurred. Lindane accumulated chiefly in the hepatopancreas. Evidence for its translocation and depuration was shown. No sexual differences occurred. 3. Tissue oxygen consumption. Both toxicants caused a depression. Recovery occurred with time. The results were related to the levels of toxicant in Midlands waters.